Perkembangan Pendidikan Islam di Afrika Utara: Pendidikan Islam di Sudan - Nurainiah Nurainiah (2022)
Education in Sudan is free and compulsory for all children aged 6 to 13 years. Education starts with basic education for eight years, then secondary education for three years. The education level was changed to 6+3+3 format in 1990. The language of instruction used at all levels is Arabic. School locations are concentrated in a number of urban areas, a number of schools in the South and West have been damaged or even destroyed by the conflict. In the field of formal education, Sudan has many well-known universities that are tens or even hundreds of years old. Among these universities are Khartoum University, Omdurman Islamic University, El-Nilein University, Khartoum International Institute of Arabic, Al Quran Al Karim University and the youngest is the International University of Africa. The education system in Sudan starts with Primary School, then Secondary School. The level above it is Vocational/Technical Education and Training or University/College Education. In addition, there are Preservice Teacher Training and In Service Teacher Training. Non-formal education, in Sudan there are many scientific assemblies that use the talaqqi system through masyakhs who are spread almost all over Sudan.